Music technology - Jackson, Tom 1972- (Brown Bear Books, 2015)
"We carry our fvorite songs with us in small pocket-sized players today--and listen to them whenever we want to. But how did people enjoy music in the past?,"--page [4] of cover
Includes bibliographical references (page 31) and index
Introduction -- Phonograph -- Gramophone -- Radio Set -- Record Player -- Portable Radio -- Hi-Fi -- Tape Deck -- Compact Disc -- Going Digital -- Music Apps -- Modern Sounds -- The Future of Music -- Glossary -- Further Resources -- Index
Keywords: Music and technology / Juvenile literature; Electronic music / Juvenile literature; Music and the Internet / Juvenile literature; Digital music players / Juvenile literature